Penerapan Algoritma C4.5 Untuk Rekomendasi Mentor Santri Baru - Adiat Pariddudin; Fajri Syabani Warsa (Universitas Binaniaga Indonesia, 2023)
The acceptance of new students is something that is routinely carried out by pesantren every year. The very large number of students and the limited number of teaching staff which can have an impact on the ineffectiveness of the activities of the educational process in the pesantren environment. This is common and has been predicted to always occur at every new student admission. The pesantren has also taken steps to anticipate this phenomenon that usually occurs every year, namely by selecting mentors for new students. In the selection of mentors for new students, the pesantren chose seniors who had been studying at the pesantren for a long time. By choosing an accurate mentor, the mentor function can be more effective. These results were tested for accuracy using the confusion matrix formula with an accuracy of 87.5%.